Scoping Review: The Role of Family Emotional Support in Reducing the Risk of Baby Blues among Postpartum Mothers - Fitrio Deviantony; Wahyu Dini Candra Susila; Salwa Nirwanawati; Robby Prihadi Aulia Erlando (STIKes Patria Husada Blitar, 2026)
The postpartum period is a sensitive transitional phase that may triggeremotional changes known as baby blues syndrome. This scoping reviewaims to explore and map the existing scientific evidence regarding the roleof family emotional support in reducing the risk of baby blues amongpostpartum mothers. Following the PRISMA-ScR guidelines, acomprehensive literature search was conducted on PubMed andScienceDirect databases for articles published between 2020 and 2025. Outof 331 identified articles, 10 open-access primary studies met the inclusioncriteria and were analyzed narratively. he results indicate that emotionalsupport from close family members, particularly husbands and parents, playsa significant role in helping mothers adapt psychologically. Key barriers tooptimal support include social stigma surrounding maternal mental health,weak family communication, and a lack of standardized screening protocolsin healthcare facilities. Conversely, crucial facilitators include active spousalinvolvement in infant care, family-centered psychoeducation, and theutilization of digital health platforms. In conclusion, family emotionalsupport serves as a vital protective factor that strengthens maternalpsychological resilience and prevents the progression of baby blues intopostpartum depression. Based on these findings, it is suggested thathealthcare frameworks formally integrate family-based education intopostnatal care, provide continuous empathetic communication training forhealthcare providers, and strengthen community-based peer supportinitiatives.